Uma breve discussão sobre a previdência social do Brasil - Sales, Vicente Aderson Paz (2004)
Nowadays the crisis of the Social Welfare is a major concern worldwide. The deficits of social security state systems are to demand rethinking of the structure of the Governments and of the financing regime as imperative to assure the solvency of the same ones. This dissertation brings a brief discussion on theoretical aspects related to the financing regime and, specifically, on historical and legal aspects of the Brazilian Social Welfare trying to highlight the impacts of macro-economical and demographical variables that they make the Pay-As-You-Go as form of financing the system, pointing, in the sequence of the analysis, the objectives of the one of the constitutional reforms of 1998 and 2003, the ones which, although they have not caused a structural change of the financing regime, they promoted changes in the Brazilian legislation system that they seek to turn the General Social Welfare Regime make feasible in a long-term run.